Diagnostic and prognostic potential of the intra-tumoral microbiota profile in HPV-independent endocervical adenocarcinoma - Zhou, Xin; Chen, Lili; Lin, Wanrun; Zheng, Wenxin; Zhang, Huijuan; Zhou, Feng (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundMicrobial community dynamics have been involved in numerous diseases, including cancer. The diversity of intertumoral microbiota in human papillomavirus independent endocervical adenocarcinoma (HPVI ECA) is not well-characterized.ObjectiveOur objective is to delineate the intratumoral microbiota profile in HPVI ECA and investigate its potential influence on oncogenesis.MethodsWe analyzed 45 HPVI ECA cases, comprising 36 gastric-type ECA (GEA) and 9 clear cell carcinomas (CCC). We compared the microbial composition within cancerous and adjacent noncancerous tissue samples using 5R-16S ribosomal DNA sequencing. Further, we investigated the correlation between specific microbes and clinical-pathological metrics as well as patient outcomes.ResultsOur findings demonstrate notable differences in the microbial spectra between cancerous and adjacent noncancerous tissues. Amongst HPVI ECA subtypes, GEAs exhibit more microbial variations compared to CCCs. Using the Random Forest algorithm, we identified two distinct microbial signatures that could act as predictive biomarkers for HPVI ECA and differentiate between GEA and CCC. Varied microbial abundances was related to clinical characteristics of HPVI ECA patients. In addition, high levels of Micrococcus and low levels of unknown genus75 from the Comamonadaceae family were associated with poorer outcomes in HPVI ECA patients. Similarly, an abundance of Microbacterium correlated with reduced overall survival (OS), and a high presence of Streptococcaceae family microbes was linked to reduced recurrence-free survival (RFS) in GEA patients. Intriguingly, a high abundance of Micrococcus was also associated with a worse OS in GEA patients.ConclusionThe study reveals distinct microbial signatures in HPVI ECA, which have potential as biomarkers for disease prognosis. The correlation between these tumor-associated microbiota features and clinicopathological characteristics underscores the possibility of microbiome-based interventions. Our research provides a foundation for more in-depth studies into the cervical microbiome’s role in HPVI ECA.